The Nexus of Household Energy Access, Income Stability, and Economic Resilience in Sub-Saharan Africa: Integrating Multidimensional Energy Indicators with the SDGs - Muritala, Taiwo A. (International Journal of Energy Economics and Policy, 2025)
Energy poverty remains a significant barrier to sustainable economic development and resilience across Sub-Saharan Africa (SSA). Addressing this challenge is central to achieving the Sustainable Development Goals (SDGs), particularly SDG 7 (Affordable and Clean Energy) and SDG 11 (Sustainable Cities and Communities). This study investigates the intricate nexus between household energy access, income stability, and economic resilience across 20 SSA countries over the period 2010–2023. Employing a novel panel dataset constructed from the World Bank, IEA, and UNDP SDG indicators (n = 320), the analysis integrates a Multidimensional Energy Poverty Index (MEPI) and an Economic Resilience Index within a structural equation modeling (SEM) framework, augmented with fixed effects and robustness tests. The results reveal that electricity access, income stability, and governance quality significantly enhance economic resilience, with urbanization and GDP per capita also playing complementary roles. Sensitivity analysis underscores the interaction between governance and MEPI in amplifying resilience effects. The study highlights that reducing energy poverty through targeted electrification and clean cooking initiatives, coupled with institutional strengthening, can foster more resilient and adaptive economies. Policy recommendations include expanding access to clean, affordable energy; improving income stability through social protection and financial inclusion; and enhancing governance and institutional quality to maximize the socio-economic impacts of energy interventions. Future research should pursue more granular, subnational analyses and explore climate-related vulnerabilities within this nexus.